Development E-Lkpd Based On Higher Order Thinking Skills To Improve Creative Thinking Of Elementary School Students - Fitriyani Fitriyani; Fahrurrozi Fahrurrozi; Gumgum Gumelar; Fajar Rakhman; Erry Utomo; Nurkhalimah Ery (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to develop HOTS-based Electronic Learner Worksheets, knowing the assessment of three experts and the opinions of educators and students in grade VI. This research uses the learning design development research or R&D using the ADDIE model. The research subjects involved comprised three experts (media, linguists, and material experts) and grade VI students. The instrument used for data collection used in the form of a questionnaire given to media experts, linguists, and material experts obtained from the results of the study is qualitative data which is analyzed using quantitative data in the form of numerical data and interpreted with guidelines for assessment category criteria to determine product quality. The results of this study produce HOTS-based E-LKPD products that can be used at the elementary level as teaching materials for students who have met the excellent criteria with an average score of 98.9% media experts, 95% linguists, and 96.9% material experts with very feasible category to use, as well as a practicality level of 87.9% in very practical criteria and an effective level with an average of 90% in the very effective category. HOTS-based E-LKPD teaching materials are feasible, practical and effective for learning.